(untitled) (Journal of University of Babylon for Engineering Sciences, 2024)
The one-dimensional model was selected to simulate the steam reforming to produce hydrogen in a fixed-bed reactor filled with catalyst particles. The model consists of mass balance of all stream components , heat balance on gas inside the reactor and tube wall reactor. This model was solved by using MATLAB/Simulink. The simulation results have been compared with actual data to validate the model. It was found the good agreement between the main exit molar rate and reformed gas temperature from the reforming reactor and the commercial reformer. Three different control methods were designed which are proportional-integral derivative, cascade and multi-loop to maintain the exit gas temperature. A comparison between these control methods have been made by using step change at different values of feed conditions. These results show that the multi-loop controller has rapidity, very good durability, more suitable, little offset, lower overshoot and less integral absolute error.